Overall economic planning in Brazil - Frieder Meyer-Krahmer (Intereconomics, 1976)
In Brazil economic policy planning, with its beginning in the early fifties, has been undertaken for a relatively long period already. Just this fact makes it possible to analyse development, contents, significance, limitations, and chances of this planning and its realisation over a prolonged period.
Keywords: 330; Brazil